POTENSI DAN PELUANG PENINGKATAN PRODUKSI PALAWIJA DI KABUPATEN SUMBAWA - L. Sukardi (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2001)
ABSTRAK Peningkatan produksi palawija menjadi salah satu prioritas di Kabupaten Sumbawa karena selain merupakan komoditas pangan utama, juga menjadi unggulan dan andalan untuk diekspor. Peluang peningkatan produksi dapat dilakukan baik melalui intensifikasi (peningkatan produktivitas pada daerah-daerah yang produktivitasnya masih di bawah rata-rata kabupaten) maupun ekstensifikasi (pemanfaatan lahan potensial yang belum tergarap). Hasil analisis menunjukkan bahwa potensi peningkatan produksi melalui kegiatan intensifikasi berturut-turut sebagai berikut : kedelai 613,58 ton, jagung 1.078,31 ton, kacang hijau 325,77 ton, dan kacang tanah 123,10 ton. Sedangkan potensi peningkatan produksi melalui kegiatan ekstensifikasi (dihitung berdasarkan dua pendekatan), yaitu : (1) berdasarkan produktivitas aktual berturut-turut : kedelai 13.006,84 ton, jagung 19.225,20 ton, kacang hijau 5.719,16 ton, dan kacang tanah 1.271,07 ton dan (2) berdasarkan produktivitas rata-rata berturut-turut : kedelai 12.981,95 ton, jagung 19.442,21 ton, kacang hijau 5.738,15 ton, dan kacang tanah 1.300,76 ton. ABSTRACT Increasing the second crop production is one of the first priority program in Sumbawa District, because this second crop is not only the main food commodities, but also the prominent and superior export commodities. The opportunity to increase the production could be achieved both through intensification (increasing production in the area that the productivity is lower than average of the district productivity) and extensification (the use of unutilized potential land). The results of the study show that the potency of increasing of production through intensification are as follows : soybean is 613.58 tones, maize is 1,078.31 tones, mung-beans is 325.77 tones, and peanut is 123.10 tones. Meanwhile, the potency of increasing of production through extensification program (counted based on two approaches), namely : (1) based on actual production : soybean is 13,006.84 ton, maize is 19,225.20 ton, mungbean is 5,719.16 ton, and peanut is 1,271.07 ton; (2) based on average productivity that indicate : soybean is 12,981.95 tones, maize is 19,442.21 ton, mungbean is 5,738.15 tones, and peanut is 1,300.76 tones.